Perilaku Pesnorkel terhadap Ekosistem Terumbu Karang (Studi Kasus di Taman Nasional Laut Kepulauan Seribu, DKI Jakarta) - Anastasia Dian Rosalina; Yonvitner Yonvitner; Zulhamsyah Imran (Jurnal Ilmu Pertanian Indonesia, 2019)
Snorkeler behaviors which are not in accordance to snorkeling guidelines are harmful to the coral reefs ecosystem. This research aims to describe the behavior patterns of visitors when they were snorkeling, and classifying snorkeler behavior according to the potential hazard which occur in the coral reefs’ ecosystem in the Kepulauan Seribu Marine National Park. Field observations shown that behavior of visitors when they were snorkeling has the same patterns that are harmful for coral reefs ecosystem when they took photo in underwater and interact with the marine biota. The act to feed fish, stepping or stand up on coral reefs, and hold coral reefs are shown by most of the snorkelers when they were snorkeling in the study location. Grouping of snorkeler behavior shown that more than part of snorkeler respondents had characteristics and perceptions that were at high risk of the possibility of non-environmentally friendly actions. Based on the risk grading matrix of snorkeler behavior, the quantity of respondents who have the potential to pose a risk behavior to the coral reef ecosystem showed 55.56% snorkeler get into a high risk category, 33.33% in the middle risk category, and 11.11% on the low risk category.That’s mean that snorkeler behavior was harmful for coral reefs ecosystem.